Hasekura Tsunenaga w Europie – sztuka, polityka i propaganda we wczesnych stosunkach europejsko-japońskich - Tybus, Maciej (Studia Azjatystyczne, 2015)
The early relations between Japan and Europe have been established in the period of civil war and turmoil. One of the most interesting events of that time was an envoy organized by Date Masamune and headed by Hasekura Tsunenaga which set to Mexico (1613) and later on Europe (1615). Although the political and economic goals have not been achieved, on the level of cultural relations this visit was a real breakthrough. The various artworks created and exchanged between the Old Continent and Asia have served as important means of visual propaganda. Thanks to them Hasekura has become a “face” of Japan in Europe, spreading new customs and fashions. His baptism can be also understood as a sing of political ambitions, empowering the Catholic missionaries in Eastern Asia. Though in the following decades Hasekura and his mission have been covered up by the isolationist policy of the shogunate, his achievements have been rediscovered and are nowadays commemorated in a number of ways worldwide.